A glimpse into archival practices: a visit to Sarawak State Repository / Nor Hayati Kassim - Kassim, Nor Hayati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
On December 8, 2023, a group of 49 students from Class 5A and 5D, accompanied by two IMD313 (Foundation of Archives) lecturers, Miss Suhaida binti Halamy and Miss Nor Hayati bte Kassim from the School of Information Science, embarked on an academic journey to the Sarawak State Repository. The primary focus of this visit was to provide students with a hands-on experience of the activities within archival institutions, going beyond the boundaries of theories learned within the classroom. Prior to the academic visit, a comprehensive safety briefing ensured the well-being of both students and lecturers during the visit. The State Repository staff, led by Miss Dorothy, warmly welcomed us and provided an overview of the functions of the state repository.